Financial stress and health considerations: A tradeoff in the reopening decisions of U.S. liberal arts colleges during the COVID-19 pandemic - Jonah Tobin; Oliver Hall; Jacob Lazris; David J. Zimmerman (Journal of Risk and Financial Management, 2021)
This paper presents empirical evidence on factors influencing choices made by members of the Annapolis Group of Liberal Arts colleges regarding whether to operate primarily in-person, primarily online or some flexible alternative during the COVID-19 pandemic of 2020. This paper examines the tradeoff between public health risks and financial standing that school administrators faced when deciding reopening plans. Because in-person instruction at colleges and universities had large effects on COVID-19 case rates, it is critical to understand what caused these decisions. We used binary and multinomial probit models to evaluate an original data set of publicly available data as well as data from the College Crisis Initiative. Binary and multinomial choice model estimates suggest that conditional upon the prevailing level of COVID-19 in their county, financially distressed colleges were approximately 20 percentage points more likely to opt for primarily in-person operations than less financially distressed colleges. These choices highlight an important potential tradeoff between public health and financial concerns present in the higher education sector and emphasize the need for public spending to mitigate adverse health outcomes if a similar situation occurs again.
Keywords: 330; COVID-19; colleges and universities; financial stress; public health